2010
DOI: 10.1134/s1054660x1009001x
|View full text |Cite
|
Sign up to set email alerts
|

Energy barriers for vortex nucleation in dipolar condensates

Abstract: We consider singly-quantized vortex states in a condensate of 52 Cr atoms in a pancake trap. We obtain the vortex solutions by numerically solving the Gross-Pitaevskii equation in the rotating frame with no further approximations. The behavior of the condensate is studied under three different situations concerning the interactions: only s-wave, s-wave plus dipolar and only dipolar. The energy barrier for the nucleation of a vortex is calculated as a function of the vortex displacement from the rotation axis i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…It is found that dipolar interactions increase v Ω in prolate traps and lower it in oblate traps when compared to the pure s-wave case [161,162]. Intuitively, this makes sense because in the prolate case dipolar interactions tend to reduce R ⊥ but in the oblate case they increase it.…”
Section: Vortex In a Trapped Dipolar Bose-einstein Condensate In The mentioning
confidence: 99%
“…It is found that dipolar interactions increase v Ω in prolate traps and lower it in oblate traps when compared to the pure s-wave case [161,162]. Intuitively, this makes sense because in the prolate case dipolar interactions tend to reduce R ⊥ but in the oblate case they increase it.…”
Section: Vortex In a Trapped Dipolar Bose-einstein Condensate In The mentioning
confidence: 99%
“…(A.4) and (A.5) of Appendix A, respectively. R T F (0) is related to root mean square radius r rms by R T F (0) = √ 3r rms [43,44].…”
Section: Root Mean Square Radius Of the Condensatementioning
confidence: 99%
“…Here we use R ρ (0) = R TF (0)/ √ 3 [43]. The above relation (10) is used to study the vortex number in conventional BECs in a rotating deep optical lattice [44].…”
Section: Vortices In a Pure Dipolar Becmentioning
confidence: 99%